A triglyceride-rich lipoprotein environment exacerbates renal injury in the accelerated nephrotoxic nephritis model. (9th March 2018) - Saja, M F; Cook, H T; Ruseva, M M; Szajna, M; Pickering, M C; Woollard, K J; Botto, M
Summary: Hyperlipidaemia accompanies chronic renal disease either as a consequence of the renal dysfunction or as part of generalized metabolic derangements. Under both situations, the lipid profile is characterized by accumulation of triglyceride-rich lipoproteins (TGRLs). This lipid profile is recognized as a risk factor for cardiovascular complications. Whether it may pose a risk for renal injury as well remains unclear. A hyper-TGRL state was generated in C57BL/6 mice using poloxamer-407 (P-407) and immune complex-mediated renal injury was triggered using the accelerated nephrotoxic nephritis (ANTN) model. The hyper-TGRL animals were hypersensitive to ANTN demonstrated by greater haematuria and glomerular cellularity. These changes were accompanied by increased glomerular accumulation of CD68 + macrophages. The hypersensitive response to ANTN was not seen in low-density lipoprotein receptor knock-out mice fed with a high fat diet, where triglyceride levels were lower but cholesterol levels comparable to those obtained using P-407. These data indicate that a hyper-TGRL state might be more detrimental to the kidneys than low-density lipoprotein-driven hypercholesterolaemia during immune complex-mediated nephritis. We speculate that the hyper-TGRL environment primes the kidney to exacerbated renal damage following an inflammatory insult with increased accumulation of macrophages that may play a key role in mediating the injurious effects. Graphical Abstract: